Diet of instant noodles - New Sunday Times, (2006)
One was the envy of many riding his scrambler all over campus while another survived on half a packet of instant noodles for each meal. One pursued physical education and scaled new heights later in life while another was the first post-graduate student of the university and now an adjunct associate professor at his alma mater.